Pemanfaatan Drainase (Saluran) Air Bekas Limbah Rumah Tangga sebagai Solusi untuk Penurunan Resistansi Pentanahan (Grounding) - Dian Eka Putra (SPEJ (Science and Physic Education Journal), 2021)
This study aims to anticipate a high value of grounding resistance by utilizing drainage or waste water from household waste as a planting medium to reduce the value of grounding resistance. The research method used is an experimental method of testing and measuring at field locations. In this study, a round rod electrode is coated with copper, namely testing with one electrode rod and two electrode rods that are installed in parallel or better known as the use of a driven rod. The results showed a decrease in the value of the grounding resistance where the average value for 1 grounding rod was 18.32 ohms and 11.82 ohms for the measurement of 2 grounding rods installed in parallel. From the test results, there was a decrease in the resistance value of 59.52% for 1 electrode rod and a 51.75% decrease for 2 electrode rods, where the decrease in the resistance value in the field was caused by factors of water, humidity and used water minerals from household waste. In conclusion, housing with reddish yellow podzolic soil that is clay (high soil resistance) by utilizing water drainage is a solution to reduce grounding resistance. Keywords: Resistance, Drainage, Grounding (Grounding)